2011
DOI: 10.1074/jbc.a111.605000
|View full text |Cite
|
Sign up to set email alerts
|

Arrestin is required for agonist-induced trafficking of voltage-dependent calcium channels.

Abstract: We suggest that subscribers photocopy these corrections and insert the photocopies in the original publication at the location of the original article. Authors are urged to introduce these corrections into any reprints they distribute. Secondary (abstract) services are urged to carry notice of these corrections as prominently as they carried the original abstracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The authors demonstrated direct interaction between the GABA B receptor subunits and Ca V 2.2 channel under high stringency conditions. However, lack of interaction between the GABA B receptor and Ca V 2.2 channel was observed under resting conditions by coimmunoprecipitation in sensory dorsal root ganglion neurons (Puckerin et al, 2006), suggesting possible differences in signaling complex organization at central versus peripheral synapses. Furthermore, a direct interaction between Ca V 2.2 and G␤␥ G-protein subunits in the CNS has been also demonstrated by proteomic studies (Khanna et al, 2007;Müller et al, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…The authors demonstrated direct interaction between the GABA B receptor subunits and Ca V 2.2 channel under high stringency conditions. However, lack of interaction between the GABA B receptor and Ca V 2.2 channel was observed under resting conditions by coimmunoprecipitation in sensory dorsal root ganglion neurons (Puckerin et al, 2006), suggesting possible differences in signaling complex organization at central versus peripheral synapses. Furthermore, a direct interaction between Ca V 2.2 and G␤␥ G-protein subunits in the CNS has been also demonstrated by proteomic studies (Khanna et al, 2007;Müller et al, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…911 Recently, it has been determined that β-arrestins regulate ubiquitylation and internalization of certain non-7-TMR membrane proteins, such as TGF-β, insulin-like growth factor I receptor, calcium channels, the Na (+) /H (+) exchanger 1 and vascular endothelial cadherin. 1216…”
Section: β-Arrestins Mediate Receptor Endocytosis Ubiquitylation Andmentioning
confidence: 99%
“…Indeed, it has been reported that these receptors are not phosphorylated by the canonical G protein-coupled receptor kinases (GRKs), yet are desensitised by GRK4 in the absence of any apparent phosphorylation (Perroy et al, 2003). It has been demonstrated in chick neurons that upon activation, GABA B receptors form a complex with Ca v channels and arrestins, then are consequently internalised as a mechanism of rapid desensitisation of GABA B receptor signalling (Puckerin et al, 2006). This however, is conflicting with evidence provided by Fairfax et al, (2004) whereby GABA B receptors did not associate with arrestins and, indeed, the cAMP-dependent kinase-(PKA) mediated phosphorylation of the GABA B receptor at position Ser892 on the GB 2 subunit increases its cell-surface stability; rather than impeding its cellular function.…”
Section: Structure/function Of Gaba B Receptorsmentioning
confidence: 99%